Raising HLA-E-Restricted HIV-1-Specific Immune Responses Through T Cell Vaccination: A Hypothesis - Ho, Soon Hoe BSc (Hon) (International Journal of Clinical Microbiology, 2017)
This essay draws on recent evidences from SIV vaccination studies in rhesus macaques to argue for the potential importance of HIV-1-specific CD8+ T cells restricted by the non-classical major histocompatibility complex, HLA-E, in controlling HIV-1 replication. It then seeks to present a possible method of inducing such responses through the procedure of T cell vaccination using activated autoimmune CD4+ T lymphocytes ‘infected’ with inactivated replication-incompetent structurally intact HIV-1 particles. It is hoped that the argument presented here will interest many of those involved in HIV/AIDS research and others in the general scientific community.
Keywords: Human immunodeficiency virus-1; T cell vaccination; non-classical major histocompatibility complex; human leukocyte antigen-E; activated CD4+ T cells